The beams at the edge of physics. (May 2021) - Chapman, Kit
Abstract : Creating a new cutting-edge accelerator isn't cheap or easy. But as Kit Chapman discovers, the upcoming Facility for Rare Isotope Beams (FRIB) in Michigan promises great things for nuclear physicists especially those with applications in mind